An autopsy case of acute lymphocytic leukemia with localized massive necrosis of the liver - KAYO, Ryotaro; FUKUNISHI, Keiichi; SHIBAYAMA, Yuro; MATSUMIYA, Teisuke; ARAKI, Masato; URANO, Toru; ASAKA, Shosaku; ODA, Kosaku (Kanzo, 1995)
We reported an autopsy case, a 50-years-old man, of acute lymphocytic leukemia with localized massive necrosis of the liver. He had been suffering from acute lymphocytic leukemia for two years, and a huge low density area in the right lobe of the liver probably due to invasion of leukemic cells was detected by CT scan and ultrasonography two weeks before his death. At autopsy, a wedge-shaped necrotic lesion, which looks like infarct, was seen in the right anterior segment, but there were no obstructive lesions of the branches of portal vein or hepatic artery. Microscopically, the necrotic lesion was formed by massive necrosis. In the wedge-shaped necrotic lesion, subendothelial proliferation of loose connective tissue was noted in a large number of the sublobular hepatic veins (localized veno-occlusive disease) and leukemic cells were found to be severely invaded into the sinusoids. In the liver, in addition to the wedge-shaped necrotic lesion, focal and random coagulative hepatocellular necrosis due to DIC (disseminated intravascular coagulation) was seen sporadically. Then, we suppose that the wedge-shaped necrotic lesion was localized massive necrosis resulted from augmentation of DIC-induced hepatocellular necrosis by sinusoidal microcirculatory disturbances due to the localized venoocclusion and invasion of leukemic cells into the sinusoids.